Cellular processes underlying cerebral cavernous malformations: Autophagy as another point of view. Issue 2 (1st February 2016) - Marchi, Saverio; Retta, Saverio Francesco; Pinton, Paolo
ABSTRACT: A growing amount of evidence indicates that autophagy plays a pivotal role in a plethora of human pathological conditions. We have recently broadened the list of the so-called autophagy-related diseases, describing the involvement of defective autophagy in the pathogenesis of cerebral cavernous malformations.